Development of Mandarin Education Quiz Game Using Android-Based Multimedia Development Life Cycle - Topani, Muhammad Alfikri Maida; Azhari, Ahmad (Universitas Ahmad Dahlan, 2023)
Mandarin is a language that is widely spoken and studied by people all over the world. Parents who start enrolling their children in Mandarin language courses from an early age with the hope that their children will become accustomed and proficient in using Mandarin. However, for elementary school children, the difficulty of constructing sentences in Mandarin is a major obstacle for children in the process of learning Mandarin. The purpose of this research is to create a unity-based mandarin quiz educational game application that is useful as an alternative media in the learning process to make it easier to learn. which is useful for a. Help make it easier for tutors in learning activities teaching by utilizing media technology in the form of Android-based educational games. Help students learn Chinese HSK material with a happy feeling and don't feel bored, because the content in the educational game